Introduction to dossier. Mining extractivism in Latin America: The juridification of environmental conflicts - Rachel Sieder; Ainhoa Montoya; Yacotzin Bravo-Espinosa (Íconos)
Introduction to dossier. Mining extractivism in Latin America: The juridification of environmental conflicts